Etiology of Pancreatitis in Patients at a Tertiary Care Center - Haider, Muhammad Fahd Bin; Ali, Irfan; Zafar, Humaira; Ahsan, Mehak; Shah, Syed Zubair Hussain; Sher, Farrukh (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare etiological frequencies in patients of acute pancreatitis presenting to our setup with international data.Study Design: Cross-sectional studyPlace and Duration of Study: Department of Gastroenterology, Pakistan Emirates Military Hospital & Combined Military Hospital, Rawalpindi Pakistan, from Aug 2020 to Jan 2022.Methodology: Patients over 12 years suffering from pancreatitis were recruited using a convenience sampling technique based upon predefined criteria for diagnosis of pancreatitis on a questionnaire. Relevant basic lab tests, including chemistries and imaging, including Ultrasound abdomen and CECT abdomen, were analyzed to establish aetiology. Data were continuously uploaded into an electronic data sheet. International Consensus Diagnostic Criteria (ICDC) algorithms were applied to diagnose autoimmune pancreatitis.Results: Out of 120 patients, 74(61.7%) were males, and 46(38.3%) were females. Biliary pancreatitis was the most common aetiology 50(41.7%), followed in descending order by idiopathic 36(30%), drug-induced pancreatitis (DIP) 9(7.5%), Post ERCP Pancreatitis (PEP) 8(6.7%), tumours 5(4%), Autoimmune pancreatitis (AIP), Hypertriglyceridemia and alcohol-induced pancreatitis each 2(1.7%).Conclusion: Biliary pancreatitis has the highest frequency, followed by idiopathic and drug-induced pancreatitis.